EFFECTS OF SPECIATION ON EQUILIBRIUM FRACTIONATIONS AND RATES OF OXYGEN ISOTOPE EXCHANGE BETWEEN (PO4)AQ AND H2O - O’Neil J.R.; Vennemann T.W.; McKenzie W.F. (My University, 2003)
The effects of phosphate speciation on both rates of isotopic exchange and oxygen isotope equilibrium fractionation factors between aqueous phosphate and water were examined over the temperature range 70 to 180°C. Exchange between phosphate and water is much faster at low pH than at high pH, an observation that is similar to what has been observed in the analogous sulfate–water system. Oxygen isotope fractionations between protonated species like H3PO4 and H2PO4− that are dominant at relatively low pH and species like PO43− and ion pairs like KHPO4− that are dominant at relatively high pH, range between 5 and 8‰ at the temperatures of the experiments. In aqueous phosphate systems at equilibrium, 18O/16O ratios increase with increasing degree of protonation of phosphate. This effect can be explained in part by the relative magnitudes of the dissociation constants of the protonated species. Under equilibrium conditions, carbonate in solution or in solid phases concentrates 18O relative to orthophosphate in solution or in solid phases at all temperatures, supporting the traditional view that biogenic phosphate is precipitated in near oxygen isotope equilibrium with body/ambient aqueous fluids with no attendant vital effects.